2013
DOI: 10.1242/jeb.083550
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum exposure impacts brain plasticity and behavior in Atlantic salmon (Salmo salar)

Abstract: SUMMARYAluminum (Al) toxicity occurs frequently in natural aquatic ecosystems as a result of acid deposition and natural weathering processes. Detrimental effects of Al toxicity on aquatic organisms are well known and can have consequences for survival. Fish exposed to Al in low pH waters will experience physiological and neuroendocrine changes that disrupt homeostasis and alter behavior. To investigate the effects of Al exposure on both the brain and behavior, Atlantic salmon (Salmo salar) kept in water treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 70 publications
0
32
0
Order By: Relevance
“…While fish can habituate to some chronic stressors, sustained plasma cortisol levels similar to those used in this study have been observed in response to diverse stressors of anthropogenic and natural origins. For example, chronic exposure to aluminum, copper, selenium or low environmental pH can result in prolonged elevations in plasma cortisol levels (Craig et al 2009, Wiseman et al 2011, Kennedy & Picard 2012, Grassie et al 2013. In salmonids, sustained increases in cortisol levels are also associated with social subordination (Gilmour et al 2005) and with specific phases of the life cycle such as smolting (Nilsen et al 2008) and sexual maturation (Fuzzen et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…While fish can habituate to some chronic stressors, sustained plasma cortisol levels similar to those used in this study have been observed in response to diverse stressors of anthropogenic and natural origins. For example, chronic exposure to aluminum, copper, selenium or low environmental pH can result in prolonged elevations in plasma cortisol levels (Craig et al 2009, Wiseman et al 2011, Kennedy & Picard 2012, Grassie et al 2013. In salmonids, sustained increases in cortisol levels are also associated with social subordination (Gilmour et al 2005) and with specific phases of the life cycle such as smolting (Nilsen et al 2008) and sexual maturation (Fuzzen et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…These contaminants are all are present in concentrations that could affect fish behavior (Sloman and Wilcox 2006;Connon et al 2011;Brooks et al 2012;Fong et al, submitted). Aluminum, in particular, affects physiological homeostasis as well as learning and behavioral performance in Atlantic Salmon (Salmo salar, Grassie et al 2013). Similarly, Sandahl et al (2007) demonstrates that copper concentrations commonly found in Delta waters can produce abnormal anti-predator behaviors in Coho Salmon (Oncorhynchus kisutch).…”
Section: The Dynamics Of Predation On Fish Populationsmentioning
confidence: 99%
“…It is also an important tool in characterising coping abilities of fishes and investigating how the environment can disturb this. In a context of global change it is, for example, increasingly applied to gauge human‐induced rapid environmental change in different contexts: polluted areas (Grassie et al, ), habitat degradation (Jeffrey et al, ), exposure to tourism (Geffroy et al, ) or global warming (Beldade et al, ). In aquaculture, effects of changes in rearing conditions on cortisol titres have been intensively investigated, notably as related to the type of feed supplied (Sadoul et al, ), effects of water recirculation (Colson et al, ), or stocking density (McKenzie et al, ; Vijayan & Leatherland, ).…”
Section: Introductionmentioning
confidence: 99%